2014
DOI: 10.1165/rcmb.2012-0496oc
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90 Inhibitors Prevent LPS-Induced Endothelial Barrier Dysfunction by Disrupting RhoA Signaling

Abstract: Permeability of the endothelial monolayer is increased when exposed to the bacterial endotoxin LPS. Our previous studies have shown that heat shock protein (Hsp) 90 inhibitors protect and restore LPS-mediated hyperpermeability in bovine pulmonary arterial endothelial cells. In this study, we assessed the effect of Hsp90 inhibition against LPS-mediated hyperpermeability in cultured human lung microvascular endothelial cells (HLMVECs) and delineated the underlying molecular mechanisms. We demonstrate that Hsp90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 46 publications
1
67
1
Order By: Relevance
“…Both these agents have been previously observed in vitro to increase endothelial permeability (50)(51)(52). Conversely, in vivo studies using these agents causes varying results.…”
Section: Discussionmentioning
confidence: 99%
“…Both these agents have been previously observed in vitro to increase endothelial permeability (50)(51)(52). Conversely, in vivo studies using these agents causes varying results.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analyses and immunoprecipitation experiments were performed as described previously (9,31). Densitometry was performed using Image Studio version 3.1 from Licor and plotted as fold change from vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…However, even short-term treatment (Ͻ4 h) with Hsp90 inhibitors attenuates LPS-induced RhoA activation and signaling and protects against LPS-mediated EBD in HLMVEC (31).…”
Section: Lps Potentiates Hsp90 Chaperone Function By Inducing Pp60mentioning
confidence: 97%
See 1 more Smart Citation
“…Birukokva and coworkers (15) showed that mechanical stretch in the phase of on-going endothelial barrier injury induces RhoA signaling via interleukin-6 receptors that otherwise induce Jak and p38 MAP kinase and NF-B signaling. NO, induced during pressure-induced shedding of glycocalyx by heparanase, is known to cause nitration of proteins including RhoA, which activates RhoA signaling (72,117). Thus a number of questions remain unanswered.…”
Section: Regulation Of Endothelial Barrier By Mechanical Stretchmentioning
confidence: 99%